SMU opens representative office in Vietnam to boost knowledge exchange with businesses, academia and upskill talent pipeline locally - Singapore Management University (Institutional Knowledge at Singapore Management University, 2024)
Singapore Management University (SMU) announced the establishment of its representative office in Ho Chi Minh City, Vietnam, known as the SMU Overseas Centre Ho Chi Minh City (OCHCMC), taking a significant step in its mission to foster knowledge-sharing and regional collaboration as a gateway university in Asia. This strategic move, which follows the successful launch of SMU's two overseas centres in Jakarta, Indonesia in 2022 and Bangkok, Thailand in 2023 is part of SMU’s Vision 2025 which aims to boost Asian growth by offering a deep understanding of Asia’s economy, polity and society. By utilising the university's resources and offerings, developing its local network, and fostering new opportunities for partnerships and collaborations between SMU and Vietnamese institutions, OCHCMC will function as a catalyst, facilitator, and coordinator for SMU in Vietnam. Additionally, it will also connect interested parties such as businesses, academia, and potential students with the various programmes that SMU has to offer.